Neuromyelitis optica (Devic's syndrome): no association with the primary mitochondrial DNA mutations found in Leber hereditary optic neuropathy. Issue 1 (January 1997) - Cock, H; Mandler, R; Ahmed, W; Schapira, A H
Abstract : Devic's neuromyelitis optica is a rare syndrome characterised by the combination of acute or subacute optic neuritis and transverse myelitis, in some cases considered to be a variant of multiple sclerosis. Mutations of mitochondrial DNA (mtDNA) associated with Leber hereditary optic neuropathy (LHON) have been identified in some patients with multiple sclerosis in whom optic neuritis is a prominent early feature. Using restriction enzyme digestion of mtDNA products amplified by the polymerase chain reaction, the primary LHON mtDNA mutations at positions 3460 bp, 11, 778 bp, and 14, 484 bp have been excluded in four women with Devic's neuromyelitis optica. A mutation at 4160 bp associated in some LHON families with more widespread neurological disease was also not detected. It is concluded that the primary mtDNA mutations currently associated with LHON are not responsible for the prominence of optic nerve disease in Devic's neuromyelitis optica.